Infoselves the value of online identity - Garbasevschi, Demetra (John Wiley & Sons, 2021)
The subject of the book has been addressed in four chapters. If this were a novel and online identity its main character, the plot would most likely lie outside the six universal types of storyline exposed with the help of data mining technology (Technology Review 2016). With no clear idea about the future of online identity, we can only assume what turn its trajectory will take. And, with only two possible endings (on the one hand downfall, tragedy, demise; on the other - ascent, accomplishment, success), the emotional arc of online identity's narrative is still undecided. Expect no closure in this story, only an open-ended inquiry into the status quo. The first chapter, Identity and the Value of Self-commodification, is rooted in the assumption that our online identity has become a legitimate and implicit component of our identity system. The implication of this rather abstract claim is straightforward: to discuss who we are online, we must first understand who we are as individuals. This logic should justify the brief theoretical detour with which this book begins, and which summons some of the leading contributions within the social sciences in order to introduce the multi-dimensional system of self-identity and the fluid relationships between who we are, who we think we are and who we are told to be. Our ideas of self and identity have evolved historically with society's changing circumstances. The commercial takeover of late modernity has normalized commodification and has made promotionalism ubiquitous. As a consequence, identities too are increasingly evaluated as quantifiable goods, being both products of labor and valued objects of exchange for individuals and the commercial system of the Internet. Commodification has surreptitiously engulfed selves and identities."--